The influence of perceived landscape value on tourists' behavioral intentions in historical and cultural blocks. - Jiaojiao Du; Yilei Wang (PLoS ONE)
Historic cultural blocks are areas where a city's material cultural heritage and humanistic characteristics converge, showcasing the city's unique features and preserving rich and complete urban memories. Research on historic blocks primarily involves strategies related to protection, renewal, planning, and enhancement. However, there is a paucity of studies that explore the relationship between landscape value perception and tourist behavioral intentions from the perspective of recreation participants during the development and renewal of historic cultural blocks. This study uses the Zhongshan Road and Sifang Road historic cultural blocks in Qingdao as a case example. By collecting multi-source data such as online texts, tourist questionnaires, and interviews, and employing qualitative analysis and structural equation modeling as quantitative analysis methods, the study reveals the structural relationship between landscape value perception, place identity, and tourist behavioral intentions: (1) Landscape value perception has a significant positive effect on tourist behavioral intentions; (2) Landscape value perception has a significant positive effect on place identity; (3) Place identity, as a mediating variable, does not mediate the relationship between ecological landscape value perception and skill education value perception, but partially mediates the relationship between historical cultural value perception and recreational value perception. Based on the research results, feedback on the development effectiveness of historic cultural blocks from the perspective of recreation participants can be visually obtained. This helps identify the pain points in the renewal and development process, pinpoint the perceptual dimensions of landscape value that need improvement, and effectively enhance the multiple dimensions of landscape value perception in the blocks. This, in turn, activates the tourism vitality of historic cultural blocks and forms a virtuous cycle model for their development.